Building an Inclusive Library: The Role of Library Science in Information Access for All - Furbani, Widiastuti (PT. Anagata Sembagi Education, 2025)
Fair and equal access to information is part of human rights and an important foundation for inclusive development. However, in practice, there are still significant gaps in access, especially for vulnerable groups such as people with disabilities, the elderly and remote communities. This research aims to examine how the principle of inclusivity is implemented in library services and examine the strategic role of library science in supporting access to information for all. This research uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observations, and document studies in several public libraries, schools, and universities in Indonesia. The results showed that most libraries have started to implement inclusive principles in physical aspects, such as providing accessibility for the disabled. However, the implementation of inclusive collections and information services is still limited. Librarians play an active role as literacy facilitators and social agents, but limited training and policy support hinder their effectiveness. Structural constraints such as lack of funding and low user participation are also major challenges. The discussion points to the importance of developing a more interdisciplinary library science and libraries as social justice institutions. This research recommends the need for systemic transformation through strengthening the capacity of librarians, participation-based policies, and integrating universal design principles and user needs-based services as a foundation in realizing inclusive and sustainable libraries.